Exploring Rogeting: Implications for academic integrity (Canadian Perspectives on Academic Integrity, 2021)
Poor paraphrasing can be a sign of underdeveloped writing skills that can lead to plagiarism. One example of poor paraphrasing is Rogeting, which is the substitution of words with their synonyms using Roget’s thesaurus or other digital synonym providers. In this position paper, we discuss Rogeting as a form of poor paraphrasing that may lead to academic integrity breaches, such as plagiarism. We discuss methods of identifying Rogeted text, concluding with practical recommendations for educators about how to better support student writers so they can avoid Rogeting in favour of developing their writing skills.